Highly Efficient Cogeneration Power Plant with Deep Regeneration Based on Air Brayton Cycle - Andrii V. Rusanov; Andrii O. Kostikov; Oleksandr L. Shubenko; Dionis Kh. Kharlampidi; Viktoriia O. Tarasova; Oleksandr V. Senetskyi (Journal of Mechanical Engineering, 2019)
Today, an urgent scientific problem is the development of highly efficient, environmentally friendly, mobile, low-power cogeneration power plants that have small size and weight characteristics, and use renewable resources as fuel. Potential consumers of generated energy are enterprises located in settlements that are far from combined heat and power plants (CHPP) or thermal power plants (TPP). Supplying heat and networks to such settlements from large power facilities is difficult, and transport charges for fuel delivery are very high. A concept of creating a highly efficient cogeneration power plant based on gas turbine technologies is proposed. A thermodynamic analysis of air, simple, and regenerative Brayton cycles is carried out. On the basis of its results, in a wide varying range of operating parameters, determined are the cycle implementation conditions providing high energy efficiency. A peculiarity of the proposed design solution is the use of air as a turbine working fluid to obtain useful capacity. In this case, the heat of the air leaving the turbine is used in the combustion process in a boiler. The proposed installation can be used with any heat source. Its main advantages compared to traditional gas turbine installations are as follows: energy advantages − the mounting of the combustion chamber of a solid fuel boiler downstream of the air turbine allows using the heat of the air leaving the air turbine, thereby reducing fuel consumption in the combustion chamber and, accordingly, increasing its efficiency; technological advantages − the turbine operates on pure air, and is protected from the formation of sludge on the surfaces of its blades or their erosion if the working fluid is dirty. It does not require that external turbine cooling systems be used, which greatly simplifies its design; environmental benefits − the turbine can operate on gas produced as a result of the thermal treatment of municipal solid waste. In addition, the boiler combustion chamber operates at almost atmospheric pressure with a lower emission of harmful substances into the atmosphere.